POLICY EVALUATION OF KPPU IN THE SUPERVISION OF E-PROCUREMENT FOR THE REVITALIZATION OF TAMAN ISMAIL MARZUKI PHASE III IN 2022 - Putra, Hendrik Pratama; Juwono, Vishnu (Natapraja, 2025)
The regulation and enforcement of business competition law by Business Competition Supervisory Commission Commission (KPPU) aim to prohibit anti-competitive practices in the procurement of goods and services. The implementation of this policy is carried out by providing services to the public who suspect collusion. This study employs a qualitative method with a descriptive approach. The findings indicate that KPPU's policy in e-procurement oversight has effectively deterred perpetrators of collusive practices. KPPU has successfully applied the principle of New Public Management (NPM), which has increased public trust in the institution, as reflected in KPPU's annual reports. The number of public reports received by KPPU has increased each year, while the occurrence of tender collusion has consistently declined. However, KPPU still faces a challenge in terms of time efficiency. This issue has led to an accumulation of cases that should have already entered the investigation stage.